Synthetic aperture technique applying to medical ultrasonic imaging - Jiang Hui; Xiong Wei-Ming; Hou Chao-Buan (1996 3rd International Conference on Signal Processing : proceedings, October 14-18, 1996, Beijing, China, 1996)
A new imaging technique, ultrasonic intravascular imaging, has been developed in recent years. By putting a tiny high frequency transducer into a blood vessel, the cross sectional image of the vessel's wall can be obtained. This technique provides high quality pathological information of the vascular vessel, which is especially important in diagnosis and therapy of disease of the coronary artery. Since the number of connections between the array and the control unit is limited, the classic beamforming technique does not give a satisfactory result. The technique of synthetic aperture imaging can be employed to solve this problem. The theory of synthetic aperture imaging on a circular track and the characteristics of the returned waves are discussed in this paper, and the imaging procedures are also included. For improving the image quality, a new method, sub-aperture focusing, is developed. Finally, some computer simulation results are presented.